Readiness of University Students for Public Service - V. S. Nikolskiy; P. A. Ambarova; N. V. Shabrova; D. I. Zemtsov; A. P. Metelev (Moscow Polytechnic University, 2024)
The article examines the implementation of one of the most important axiological foundations of higher education - the formation of attitudes among students towards public service as a social value. The relevance of the study is due to the need to evaluate educational practices that perform this social function in the higher education system. The focus of attention is on the readiness of students for public service as a result of the introduction of a new pedagogical approach «Service Learning» into the education. Some research questions are analyzed: the concept of public service and its interpretation in the context of higher education; key indicators of university students' readiness for public service; opportunities for Service Learning to develop readiness for public service. It is proposed to consider public service as an activity in the interests of other people, implemented in two forms - as social and professional service. The first form is associated with the implementation of responsible and reciprocal behavior, the second form is the social mission of the profession. Based on the data of the sociological study (2024), the features and problems of forming readiness for social and professional service among students of Russian universities are shown. A significant result of the study was the fixation of changes in the personal qualities of students in the process of Service Learning, which are as predictors of their involvement in the practice of public service during and after university studies.